Complications and Management of Myocardial Infarction in Hypertensive Patients: A Review - Gani, Azhari; Hayati, Kemala (Dentistry Faculty, 2024)
Background: Myocardial infarction (MI) and hypertension are cardiovascular conditions that frequently coexist and influence each other. Hypertension not only increases the risk of MI but also complicates its clinical management. Therefore, it is crucial to understand the complications arising from this condition and the effective management strategies. Objectives: This systematic review aims to identify and analyze common complications in hypertensive patients experiencing MI and evaluate the optimal management approaches based on the latest literature. Methods: A literature search was conducted in electronic databases such as PubMed, Scopus, and Google Scholar using relevant keywords like